Manual de funciones y procedimientos para el personal de la lavadora “El Paisa” de la ciudad de Santo Domingo, provincia Santo Domingo de los Tsáchilas, año 2012. - Paspuel Loor, Silvia Johana (2013)
This thesis took her place in the facilities of the washing machine "El Paisa", located in the direction Jose Maria Egas and Abraham Calazacon of the city of Santo Domingo, Santo Domingo de los Tsáchilas province, with the aim of drawing up a manual of procedures and functions, for which it was necessary to identify the jobs which constitutes the enterprise organizational structure classified functions of human talent according to the identified areas and hierarchical levels, established lines of authority and responsibilities required by the organization. Within the methodological process to elaborate the functions and procedures manual, took into account the following points: establish the objectives of the company; Objectives, policies and support schemes; Identify and clarify the activities necessary to achieve them; Group these activities in accordance with the human talent, available materials, processes and development of actions, depending on the circumstances, delegating to each competent authority to carry out the activities. To develop the study used two types of research; field, implemented in the washing machine "El Paisa", using the techniques of surveys and interviews, which were applied to different areas of the company staff; bibliographic type - documentary, based on texts, books and the internet, based on the object of study. Also used several methods; inductive, deductive and analytic, which enabled collecting primary and secondary information according to the theme. The literary review contributed to the accomplishment of this work, also collaborated with the structure of the manual functions. It was clear to see in various positions in the company, work overload, it is generated by the lack of a manual of procedures and functions, besides the roles and responsibilities of human talent are not defined in detail. The preparation of the manual, will allow determining the functions of the personnel that work in different areas, this form will optimize the development of activities and therefore it will remedy the difficulties in administrative and operational processes. Since there is a need to optimize the work performance and organize human talent in the washing machine "El Paisa", it was necessary to establish a proposal, showing the design of the functions and procedure manual, which was structured according to the functional organization of the company, which will allow to define the functions of staff in the different areas motivating them and enabling it to carry out efficiently its activities, both administrative and operational. The purpose of the manual of procedures and functions is the optimize the development of processes, both in the Administration, as a service to the customer. Design manual is because the company presents an informal organization, which negatively affects the operational development of human talent, due to poor knowledge of the functions and processes, causing distortions at the time of taking decisions at the working level.